The Comparative Analysis of Inductor and Reluctance Wind Generators - Kamoliņš, Edmunds (Electrical, Control and Communication Engineering, 2009)
In the presented work two designs of brushless generators are compared: inductor and reluctance. Both designs are multipolar and also can be applied as directly driven wind generators. Both one and the second designs are basically similar, but in the inductor generator are windings of excitation or permanent magnets which complicate a design, increase consumption of the copper and energy losses. In work shown that reluctance generator has no winding of excitation, it is simple and more reliable, it has less weight. It's more competitive for use in low power wind plants.